PROSPECTS OF DEVELOPMENT ELECTRONIC AUTOMATIC CONTROL SYSTEMS FOR GAS-TURBINE ENGINES - Геннадий Степанович Ранченко; Анна Григорьевна Буряченко (Авіаційно-космічна техніка та технологія, 2018)
The analysis of the basic directions of electronic automatic control systems for aviation gas-turbine engines (FADEC) development is presented. This analysis is executed on the base of materials of the Scientific and Technical Congress of Aero-Engine Manufacturers. This Congress passed within the limits of the International engine forum in April 2018 in Moscow under aegis of the International association «Association of Aero-Engine Manufacturers» (ASSAD). The review of a modern condition of developing works of the specialized scientific enterprises in the field of application of onboard mathematical model «virtual engine» and introductions of wireless technologies in the aviation industry is given. It is noted, that design offices of manufacturers introduce as perspective decisions the modular unitized design for electronic automatic control systems and the “vibration passport” for engine type. The using of onboard mathematical model «virtual engine» provide the electronic automatic control systems with the possibility to apply the new controlling concepts and to compensate the failures of transducers which have information interchange with the automatic control system. The software «virtual engine» is developed by scientists of Central Institute of Aviation Motors (Moscow) and of Ukrainian National Aerospace University (Kharkov). The wireless technologies need the specialized power supply devices for wireless engines transducers. There is the tendency to use the engine energy (thermal engine energy, vibration engine energy) for such a power supply devices which is to be built on the base of thermoelectric generators, vibration generators and magnetic induction generators. The investigation of engine vibration characteristics in order to form the “vibration passport” for engine type is described. This passport is to be used for engine diagnostic during exploitation. There is described the method of electronic automatic control systems reliability confirmation by comparison with the prototypes (analogs) which is proposed by scientists of Central Institute of Aviation Motors.